Creating Dissonance: Self-Tracking Devices and their Effects on Users - Xenia Schmidli (Current Issues in Sport Science)
This paper explores the challenges that appear to emerge with the continuous everyday use of wearable devices for physical activity tracking. With self-tracking becoming one of the leading fitness trends over the last few years, the effects these devices have on the user warrant further investigation.